Программирование микроконтроллеров MCS-51 - Солдатов А. А. Андрей Алексеевич; Торгаев С. Н. Станислав Николаевич; Васнев Н. А. Николай Александрович; Тригуб М. В. Максим Викторович; Мусоров И. С. Илья Сергеевич (Томск, Изд-во ТУСУР, 2017)
В фонде НТБ ТПУ отсутствует